β-Glucosidase-pretreated black goji berry tea reduces glucose release and enhances bile acid binding co-digestion with high-fat meals in simulated digestion - Kritmongkhon Kamonsuwan; Thanaporn Kaewpradup; Charoonsri Chusak; Suvimol Charoensiddhi; Scott Smid; Sirichai Adisakwattana (Scientific Reports)
Abstract Black goji berry (BGB) has gained attention for its reported health benefits, but its specific effects as a tea infusion and the potential enhancement by β-glucosidase treatment remain unexplored. β-glucosidase is known to enhance the release of bioactive compounds from their glycosylated forms, potentially improving their biological activities. This study aims to evaluate the biochemical and biological properties of BGB tea, focusing on how β-glucosidase treatment influences anti-hyperglycemic, bile acid binding, and antioxidant activities. BGB tea infusions (5–30% w/v) showed concentration- and time-dependent increases in phenolic (TPC), flavonoid (TFC), and anthocyanin content (TAC), along with enhanced α-amylase and α-glucosidase inhibition. Optimal β-glucosidase treatment (20 units/mL, 10 min) increased phenolic, flavonoid, and anthocyanin content by 4.19%, 8.80%, and 9.44%, respectively. Furthermore, α-amylase and α-glucosidase inhibition improved by 2.15-fold and 1.4-fold, respectively. Simulated digestion models showed that β-glucosidase-treated BGB was significantly more effective than untreated BGB in reducing glucose release and improving bile acid binding, with the 1:2 meal-to-BGB ratio identified as optimal for these effects. Antioxidant activity was enhanced in both treated and untreated BGB, showing comparable improvements. These findings suggest β-glucosidase-pretreated BGB tea can reduce glucose release, improve bile acid binding, and enhance antioxidant activity when co-digested with meals.